The Effect of Artemisia absinthium Hydroalcholic Extract on Ovaries and Pituitary- Gonadal Axis Hormones in Mice - Shokouh chegini; Mina Ramezani; Solmaz Shahla (Journal of Ardabil University of Medical Sciences, 2018)
Background & objectives: Artemisia absinthium (known as wormwood) is used as an antihelminthical, antimalarial, antiseptic and  anti-inflammatory agent, and is used for treatment of gastric pain in the traditional medicine. In the present study, we evaluated the effects of hydroalcoholic extract of A. absinthium on the ovary tissues and pituitary_gonadal axis of the adult female NMRI mice. Methods: In this experimental study, intraperitoneally (IP) injections of hydroalcoholic extract of A. absinthium, were performed over 30 days on 50 mice with 50 (first group), 100 (second group), and 150 mg/kg.bw (third group) doses.  The sham group was received distilled water and control group received no injection. After 30 days of injections, the animals were dissected, and blood samples were collected by heart aspiration.  The levels of LH, FSH, estrogen and progesterone of serum were measured by ELISA method. Seven µm sections of ovary were prepared by a microtome and stained by H&E method. Data were analyzed by One-Way ANOVA and Tukey post- hoc test. The Significance level was set at p<0.05.        Results: Our findings indicated a significant reduction (p<0.05) in the body weight in all experimental groups compared with sham and control groups. In parameters such as: large and small diameters of the ovary , number of primary, secondary, growing, graafian follicles, and corpus luteum, a significant decrease was observed in 100 and 150 mg/kg doses (p<0.05). In all experimental groups, no significant changes were observed in estradiol and progesterone levels. However, FSH and LH showed a significant decrease in 100 and 150 mg/kg doses (p<0.05). Conclusion: Therefore, it can be concluded that Artemisia absinthium hydroalcohlic extract in high doses has damaging effects on the process of oogenesis, which may be due to α and β Thujoun, Alkaloid and Saponin constituents in this plant.